Transfer process of the ACACIA Center Model: An organizational learning scenario - Guevara Bolaños, Juan Carlos (2021)
The ACACIA Centers are university dependencies created with the purpose of promoting university integration to produce didactic and technological resources and the generation of strategies aimed at the inclusion and accessibility of all members of the university community. This article describes the process that allows the transfer of the ACACIA Center model to Higher Education Institutions interested in implementing a Center and the results achieved so far.